Pelatihan Pembuatan Pestisida Alami Dari Kulit Bawang Merah Dan Bawang Putih Dalam Upaya Pemanfaatan Limbah Rumah Tangga Di Desa Reban Sebagai Wujud Pengimplementasian Nilai Pancasila - Mifrotun Khasanah; Raihan Fajri Muharrom; Erisandi Arditama (Universitas Negeri Semarang, 2026)
The training on making natural pesticides from onion and garlic peels in Reban Village aims to educate the community on effectively utilizing household waste. Onion peels, often considered as waste, are processed into environmentally friendly and safe pesticides for agricultural use. This training is also an effort to implement the values of Pancasila, particularly in terms of environmental preservation and mutual cooperation. Through this program, it is expected that the Reban Village community will increase their awareness of the importance of utilizing household waste and adopt a more sustainable lifestyle. The results of this training indicate that the community is capable of producing effective natural pesticides while also strengthening a sense of togetherness and care for the surrounding environment.